Inadvertent malposition of a permanent ventricular lead into the middle cardiac vein was misdiagnosed as lead perforation - Mingxian Chen; Zhihong Wu; Zhenjiang Liu; Lin Hu; Xuping Li; Qiming Liu; Shenghua Zhou (Annals of Noninvasive Electrocardiology, 2022)
Abstract A 54‐year‐old man had a dual‐chamber pacemaker implantation 9 years ago because of sick sinus syndrome at a different facility. The patient did not undergo any evaluation of his pacemaker for a long time with cardiologist. The patient was admitted to another hospital manifesting dyspnea and palpitation with atrial fibrillation for 1 month, and he was diagnosed with ventricular lead perforation. For further treatment, he was referred to our hospital, and an elective replacement indicator (ERI) of the battery state and a malpositioned ventricular lead into the middle cardiac vein were found. Finally, the pacing lead was left in the primary place and the pacemaker was replaced.